An experimental-analytical scale-linking study on the crack-bridging mechanisms in different types of SHCC in dependence on fiber orientation. (February 2022) - Curosu, Iurie; Muja, Erjon; Ismailov, Mansur; Ahmed, Ameer Hamza; Liebscher, Marco; Mechtcherine, Viktor
Abstract: A scale-linking, experimental study complemented by an analytical model was carried out to investigate the influence of fiber orientation on the crack-opening behavior of strain-hardening cement-based composites (SHCC). Three SHCC compositions were investigated with polyvinyl alcohol (PVA) and ultra-high molecular weight polyethylene (UHMWPE) fibers in combination with normal- and high-strength matrices. The micromechanical experiments with fiber inclinations of 0°, 30°, 45°, and 60° involved fiber embedment in plain and fiber-reinforced specimens. The experimentally derived micromechanical parameters were input into an analytical crack-bridging model to assess the upscaling accuracy of the micromechanical results by comparing the predicted crack-bridging laws to the single-crack opening behavior of equivalent miniature SHCC specimens with controlled fiber orientation. This study yields new insights into the effect of fiber orientation on the crack-bridging properties of different types of SHCC, assesses the link between micromechanical and composite scale properties, offers a solid experimental basis for refining the analytical models, and developing anisotropic materials models for SHCC in dependence on fiber orientation. Highlights: The micromechanical parameters are highly sensitive to the testing configuration, embedded length, and material composition; Dispersed fibers have a positive effect on the pullout strength of PE fibers and no considerable effect in the case of PVA; The inclination of PE fibers has a negative effect on the apparent bond strength; Fiber rupture with increasing fiber inclination limits the accuracy of the analytically derived crack-bridging relationships.